The geopolitical vs. the network political: Internet designers and governance. (1st September 2013) - Braman, Sandra
With the recognition that communication networks in general and the Internet in particular are not only infrastructural but socio-technical in nature comes the responsibility to think such networks through from the perspective of how they influence – and/or are – forms of power and governance. The notion of citizenship is one that appears relative to both social and technical systems, and thus at their conjuncture, because it is the concept through which the rights and responsibilities of individuals relative to governance are refracted. It was in fact the case that citizenship was a concern for those responsible for technical design of the Internet as that history both unfolded through and is recorded in the technical document series known as the Internet Requests for Comments, or RFCs. This paper analyzes the two types of citizenship of concern from the perspective of Internet design – geopolitical (oriented around the state) and network political (oriented around the network) – and interactions between the two as they were discussed within and affected the Internet design process. These network-inspired ideas about citizenship in turn contribute to the ongoing discussion about the evolution of new forms of citizenship in today's environment, including in particular those that are global and/or technological in nature.